Automatic Removal of Typed Keystrokes From Speech Signals - Acero, Alex; Seltzer, Mike (IEEE Signal Processing Letters, 2007)
Computers are increasingly being used to capture audio in various applications such as video conferencing and meeting recording. In many of these applications, user may be simultaneously typing on the keyboard, e.g., to take notes or search for information. As a result, the captured speech signals are significantly corrupted by sounds generated by the user’s keystrokes. In this paper we propose an algorithm to automatically detect and remove keystrokes from speech signals. The proposed method does not require any user training or enrollment and is computationally efficient. The keystroke removal algorithm generates significantly enhanced speech as measured by both user listening tests and speech recognition experiments.